Coagulation disorders secondary to acute liver failure in Amanita phalloides poisoning: A case report - Dilek SOYSAL; Çetin ÇEVİK; Aras SAKLAMAZ; Yeşim YETİMALAR; Belkıs ÜNSAL (Turkish Journal of Gastroenterology, 2019)
-